2002
DOI: 10.1124/jpet.300.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Cilostazol against Focal Cerebral Ischemia via Antiapoptotic Action in Rats

Abstract: This study examined the protective effects of cilostazol on cerebral infarcts produced by subjecting rats to 2-h occlusion of the left middle cerebral artery followed by 24-h reperfusion. The ischemic cerebral infarct consistently involved the cortex and striatum. The infarct size was significantly reduced, when rats received 10 mg/kg cilostazol intravenously 5 min or 1 h after the completion of 2-h ischemia. Cyclic AMP level was significantly elevated in the cortex of 4-and 12-h reperfusion (P Ͻ 0.01) followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 34 publications
6
101
0
2
Order By: Relevance
“…Previous studies (20,21) have shown that cilostazol reverses decreases in Bcl-2 protein and increases in Bax protein production and cytochrome c release. The maxi-K channel opening-coupled upregulation and down-regulation of PTEN phosphorylation with resultant increases in Akt and CREB phosphorylation and increased Bcl-2 protein levels have also been demonstrated (12).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies (20,21) have shown that cilostazol reverses decreases in Bcl-2 protein and increases in Bax protein production and cytochrome c release. The maxi-K channel opening-coupled upregulation and down-regulation of PTEN phosphorylation with resultant increases in Akt and CREB phosphorylation and increased Bcl-2 protein levels have also been demonstrated (12).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that Bid was processed by caspases in NOinduced apoptosis (21,52). However, the molecular role of Bid in NO-induced apoptosis has not been fully delineated.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations